(untitled) (New York, 2006)
This book examines the multiple aspects of partner stalking from the victim's perspective. Female survivors share their personal stories of partner stalking, and the authors provide an extensive look at the latest stalking research providing readers with the new most relevant implications for practice and future research.
Keywords: Women,Abused women,Phụ nữ,Lạm dụng phụ nữ; Crimes against,Chống lại tội ác